(untitled) (Bangladesh Journal of Medical Microbiology, 2011)
The present study was conducted in the department of Microbiology, Dhaka Medical College, Dhaka during the period of January, 2007 to December, 2007. Urine samples were collected from 86 dyspeptic patients undergoing upper Gastrointestinal Tract (GIT) endoscopy to determine anti-H. pylori IgG antibody by an ELISA method. Gastric biopsy tissues were tested for culture, rapid urease test and H&E/Giemsa stain. Out of 86 endoscopic biopsy specimens, 45 (52.33%) were culture positive, 63 (73.26%) were rapid urease test positive and 64 (74.42%) were H&E/Giemsa stained positive for H. pylori. According to operational standard definition, among the 86 study population, 66 (76.74%) were H. pylori infected, 16 (18.60%) were uninfected and 4 (4.65%) were indeterminate. Among 66 H. pylori infected cases, 63 (95.45%) were urine ELISA positive and among 16 uninfected cases 3 (18.75%) were urine ELISA positive. Out of 86 study population, 66 (76.74%) were urine ELISA positive. The sensitivity, specificity, PPV, NPP and accuracy of urine ELISA were 95.45%, 81.25%, 95.45%, 81.25% and 92.68% respectively. The result of the study shows that H. pylori infection can be rapidly and reliably diagnosed by detecting anti-H. pylori IgG from urine. Key words: H. pylori; ELISA; GIT; IgG. DOI: http://dx.doi.org/10.3329/bjmm.v4i1.8463 BJMM 2011; 4(1): 14-17